Carbon Dioxide Laser in the Treatment of Oral and Craniofacial Soft Tissue Lesions, Pros and Cons - Sahar Abdualkader Ismaeel1 , Saif Saadedeen Abdulrazaq2 , Alaaaldeen Abass Alani3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background and objectives: Whether to use a cold scalpel or laser surgery to remove a lesion in the skinof the craniofacial area is the main question the surgeon asks him- or herself to do. The study tried to extendthe literature with data that may help the surgeons to choose the right method.Methods: Thirty patients with intra- and extraoral craniofacial skin lesions managed by Carbone dioxide(CO2) laser surgery.Results: The most common type of lesion treated was melanocytic nevi (15 patients; 50%).Conclusion: The main complication of CO2 laser surgery is the remaining permanent hypopigmentation ofthe treated area; however, the CO2 laser has many advantages (especially at the time of surgery) making ita good choice for the management of these lesions.